Im trying to solve $$\int_{-\infty}^{\infty}\frac{x^2 \cos(x)}{(x^2+1)^2}dx$$ using the method of residues. This function has two simple poles at $x=\pm i$ and so $$\int_{-\infty}^{\infty}\frac{x^2 \cos(x)}{(x^2+1)^2}dx=2\pi i\text{Res}_{z=i }\frac{z^2 \cos(z)}{(z^2+1)^2}=2\pi i \lim_{z\to i} \frac d{dz}\Big[ (x-i)\frac{z^2 \cos(z)}{(z^2+1)^2}\Big]=2\pi i\lim_{z\to i}\frac d{dz}\Big[\frac{z^2\cos(z)}{(z+i)^2} \Big]=2\pi i \lim_{z\to i} \Big[ \frac{(z+i)^2(2z\cos z-z^2 \sin z)-2z^2(z+i)\cos z}{(z+i)^4} \Big]=2\pi i(-\frac{ei}{4})=\frac{\pi e}{4}$$ However wolfram alpha says that $$\int_{-\infty}^{\infty}\frac{x^2 \cos(x)}{(x^2+1)^2}dx=0$$ I'm almost certain that the residue calculated above is correct, so why am I not able to apply the method here?

  • $\begingroup$ Since it is even function, the integration is not zero. $\endgroup$ – duanduan Dec 19 '16 at 6:04
  • $\begingroup$ @duanduan But the integral is zero $\endgroup$ – gene Dec 19 '16 at 6:23
  • 1
    $\begingroup$ On which closed curve are you integrating? $\endgroup$ – mathcounterexamples.net Dec 19 '16 at 6:30
  • 2
    $\begingroup$ your application of the residue theorem is wrong $\endgroup$ – tired Dec 19 '16 at 10:03
  • $\begingroup$ 'I'm almost certain that the residue calculated above is correct' ---No, your calculation is wrong. \begin{align}\int_{-\infty}^\infty \frac{x^2\cos x}{(x^2+1)^2}dx&=\int_{-\infty}^\infty \frac{\cos x}{x^2+1}dx-\int_{-\infty}^\infty \frac{\cos x}{(x^2+1)^2}dx\\&=\frac{\pi}{e}-\frac{\pi}{e}=0.\end{align} $\endgroup$ – ts375_zk26 Dec 19 '16 at 12:18

Let $C$ be a closed contour comprised of $(i)$ the real-line segment from $-R$ to $R$ and $(ii)$ the semi-circular arc of radius $R$, centered at the origin, and in the upper-half plane. Then, we have for $R>1$

$$\begin{align} \oint_C \frac{z^2e^{iz}}{(z^2+1)^2}\,dz&=2\pi i \text{Res}\left(\frac{z^2e^{iz}}{(z^2+1)^2},z=i\right)\\\\ &=2\pi i \lim_{z\to i}\frac{d}{dz}\left(\frac{z^2e^{iz}}{(z+i)^2}\right)\\\\ &=2\pi i \lim_{z\to i}\left(\frac{2ze^{iz}+iz^2e^{iz}}{(z+i)^2}-\frac{2z^2e^{iz}}{(z+i)^3}\right)\\\\ &=2\pi i \left(-ie^{-1}/4 +ie^{-1}/4\right)\\\\ &=0 \tag 1 \end{align}$$

We also have

$$\begin{align} \oint_C \frac{z^2e^{iz}}{(z^2+1)^2}\,dz&=\int_{-R}^R\frac{x^2e^{ix}}{(x^2+1)^2}\,dx+\int_0^\pi \frac{R^2e^{i2\phi}e^{iRe^{i\phi}}}{(R^2e^{i2\phi}+1)^2}\,iRe^{i\phi}\,d\phi \tag 2 \end{align}$$

As $R\to \infty$, the second integral on the right-hand side of $(2)$ approaches zero. Therefore, putting everything together we find that


and therefore since $e^{ix}=\cos(x)+i\sin(x)$



Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.